Corporate, operational, and information systems strategies: Alignment and firm performance (2020)
This study investigates the effect of the alignment between corporate, operational, and information systems strategies and firm performance. Data were collected from the application of 138 questionnaires to large utility companies in the Australian electricity sector. In the analysis, modeling using structural equations was used to establish the dependency relationship between the variables. The results suggest that aligning operational and information systems strategies can improve firm performance. Likewise, no direct effect of corporate strategy on the firm performance was found.